PENGARUH MOBILISASI AKTIF TERHADAP PENCEGAHAN HIPOTENSI ORTHOSTATIK PADA PENDERITA DIABETES MELLITUS DENGAN HIPERGLIKEMI - Ahmad Efrizal Ammrullah (Jurnal Kesehatan dr. Soebandi, 2014)
Study about Diabetes Mellitus has showen the increases of its prevalention. Approximately in year 2002 there are 150 million patients in the world, year 2003 are 194 million, and year 2005 are 330 million. Diabetes Mellitus is one disease that can causes complications in many bodies organ, one of them due to circulation system and manifestating as orthostatic hypotension. Diabetes Mellitus is an endocrine metabolic disease with the chronic hyperglicemic, its sign decrease or none of insulin production. The disorder manifestation to circulation system is orthostatic hypotension, was define to acute blood pressure decrease (systole > 20 mmHg and diastole > 10 mmHg). To prevent this condition, nursing intervention that can doing is active mobilization. The aim to this study to know the influence of active mobilization to prevent orthostatic hypotension to Diabetes Mellitus with hyperglicemic. Its design was Quasy-Experimental with pre and post test design. It was held on November 2005 and located in IRNA I Saiful Anwar General Hospital. Sample was taken by used purposive sampling with 20 persons to experiment group and 20 persons to control group. The data analyze using Chi-Square test. In significant level 95% X2 = 6,667, degree of freedom (df) = 1, got result p-value = 0,010. it means there is a significant influence active mobilization to prevent orthostatic hypotension to Diabetes Mellitus with hyperglicemic. The next study is needed to do the instrument test first to get the exactly active mobilization technique to prevent orthostatic hypotension to Diabetes Mellitus with hyperglicemic, because this condition is still happen in many patient.